The role of authority and context in shaping leadership processesand distribution in business school departments: an exploratory study - Rothenberg, Neil (Cranfield University, 2015)
Since the turn of the century interest has grown in alternative models of leadership to reflect increased complexity and ambiguity, the need to respond faster to complex market conditions, and new patterns of accountability, inter- dependency and co-ordination within organisations of all types. This has led to the emergence of alternative models of leadership including shared and distributed leadership. In many organisations, such as those with matrix structures, many leaders need to accomplish organisational goals without formal line management authority over employees. This is also the case in many professional services (e.g. law and consultancy) that operate partnership models whereby individuals have little direct authority over their peers. In University settings the governance structure also impedes traditional hierarchical leadership. The tenure system, operated by many universities and colleges in the United States and Canada, provides intellectual autonomy, protects academics from external pressure and offers job security. Despite a growing literature on shared and distributed leadership, few studies have empirically examined the nature of leadership distribution, the contextual factors that impact leadership, and how those in senior positions (e.g. university department chairs) achieve organisational goals when employees (e.g. faculty members) possess significant authority and autonomy. This study addresses this gap. In so doing the study aims to contribute to the literature on shared and distributed leadership and provide important insight to assist positional leaders who possess limited direct authority in more effectively accomplishing their leadership goals. ...[cont.]
Keywords: Department leadership; Distributed leadership; Contextual leadership